The Patchwork Text as Assessment Tool for Postgraduate Law Teaching in South Africa - Horn, JG; Van Niekerk, L (Obiter, 2020)
In the increasingly competitive higher education sphere, delivering graduates with a sound academic grounding in their discipline is no longer enough. Institutions of higher learning must yield lifelong learners who are employable and equipped with the practical skills required by the profession. To ensure this, the right assessment approach is key. While assessment has always been a crucial component of instruction, traditional assessment tools run the risk of being mere tools for certification, facilitating surface learning instead of deep learning. Assessment approaches need to be re-evaluated to strike a balance between encouraging deep learning and instilling proper academic knowledge in graduates. To contribute to such a re-evaluation of traditional assessment methods, this article reports on the introduction of the patchwork text (PWT) as an alternative assessment tool in postgraduate law teaching at the University of the Free State (UFS). After making the case for the move towards more authentic, alternative assessment techniques, the authors embark on a discussion of the main features of the PWT, as well as guidelines for drafting a PWT assessment. The focus then shifts to an overview of PWT implementation in other postgraduate modules, ending with a discussion of the authors’ experience introducing the PWT in their own teaching. Useful information about the authors’ approach is shared, including examples of formative assessment exercises used as part of the PWT, specifics regarding the portfolio of evidence of learning to be handed in, and an outline of the four “patches” making up the assessment. It is concluded that the PWT has proven to be a viable tool for assessing postgraduate students in certain law modules at the UFS. It has managed to promote deep learning, develop students into critical thinkers and problem-solvers, and compel them to continuously engage with the study material – all while achieving the intended learning outcomes. The PWT is therefore recommended to lecturers who seek to equip students with a macro-vision of their field of study, the ability to integrate and contextualise different areas of the discipline, and the skill to reflect critically on new, emerging developments in the field.